Biocatalytic Desulfurization Capabilities of a Mixed Culture during Non-Destructive Utilization of Recalcitrant Organosulfur Compounds - Ismail, Wael; El-Sayed, Wael S.; Abdul Raheem, Abdul Salam; Mohamed, Magdy E.; El Nayal, Ashraf M. (Frontiers in Microbiology, 2016)
We investigated the biodesulfurization potential of a mixed culture AK6 enriched from petroleum hydrocarbons-polluted soil with dibenzothiophene (DBT) as a sulfur source. In addition to DBT, AK6 utilized the following compounds as sulfur sources: 4-methyldibenzothiophene (4-MDBT), benzothiophene (BT), and 4,6- dimethyldibenzothiophene (4,6-DM-DBT). None of these compounds supported the growth of AK6 as the sole carbon and sulfur source. AK6 could not grow on dibenzylsulfide (DBS) as a sulfur source. The AK6 community structure changed according to the provided sulfur source. The major DGGE bands represented members of the genera Sphingobacterium, Klebsiella, Pseudomonas, Stenotrophomonas, Arthrobacter, Mycobacterium and Rhodococcus. Sphingobacterium sp. and Pseudomonas sp. were abundant across all cultures utilizing any of the tested thiophenic S-compounds. Mycobacterium/Rhodococcus spp. were restricted to the 4-MDBT culture. The 4-MDBT culture had the highest species richness and diversity. Biodesulfurization of DBT by resting cells of AK6 produced 2-hydroxybiphenyl (2-HBP) in addition to trace amounts of phenylacetate. AK6 transformed DBT to 2-hydroxybiphenyl with a specific activity of 9 ± 0.6 µM 2-HBP g dry cell weight-1 h-1. PCR confirmed the presence in the AK6 community of the sulfur-specific (4S) pathway genes dszB and dszC. Mixed cultures hold a better potential than axenic ones for the development of a biodesulfurization technology.